Implementasi Kebijakan Good Governance Pada Sekretariat Daerah Kota Bitung - Rorong, Meirando E.; Lengkong, Florence Daicy; Ogotan, Martha (Sam Ratulangi University, 2016)
Abstract :The problem of bureaucracy faced by all local goverments pertaining to theimplementation of Good Governance, because it is not become institutionalized yet, inlocal government neither from the strucutral and cultural aspects nor fromnomenclature program that support it. Besides, there is no skill human resource thathas capability in his field, became one of the factors that cause bureaucracy of a localgoverment not effective. Based on that fact, it can be said that up to now, theimplementation of good governance in local government is only a slogan. Thisbecomes the reason of the researcher to analyze the implementation of agoodgovernment policy at secretariat office Bitung City. The purpose of this research is: (1)To analyze and describe the implementation of transparency at Secretariat Office inBitung City; and (2) To analyze and describe the implementation of accountabilityprinciples at Secretariat Office in Bitung City.Method used in this research was descriptive qualitative method. The data wascollected through: direct interview and field observation. The informant was chosenwith the purpose to describe social symptom a certain social problem based on a certainconsideration which was called purposive sampling. The informants were 7 employeesfrom the Secretariat Office in Bitung City, consisted of 5 structural employee (eselonII,III and IV), and 2 from non structural employee with consideration that they knowmore about the problem.The research findings, revealed that: (1) The implementation of transparencyprinciple at Secretariat Office in Bitung City was good enough. For that reason, it isrecommended that the transparency and accountability needed to be increased for therealization of optimal good governance policy in harmony with the expectation oforganization and community of Bitung City.Keywords: Transparency, Accountability, Implementation of GoodGovernance.